2018
DOI: 10.1186/s12872-018-0748-x
|View full text |Cite
|
Sign up to set email alerts
|

Cold exposure induced oxidative stress and apoptosis in the myocardium by inhibiting the Nrf2-Keap1 signaling pathway

Abstract: BackgroundExposure to cold weather is associated with infaust cardiovascular responses, including myocardial infarction and arrhythmias. However, the exact mechanisms of these adverse changes in the myocardium under cold stress are unknown. This study was designed to investigate the mechanisms of cardiac injury induced by cold stress in mice.MethodsThe mice were randomly divided into three groups, normal control (no handling), 1-week cold stress and 2-week cold stress. We observed physiological changes of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 53 publications
5
32
0
Order By: Relevance
“…These differences may be related to the extent and duration of cold stress in different experiments. Evaluation of cardiac function using echocardiography has indicated that cold stress decreases in ejection fraction and shortening fraction of mouse hearts, leading to dampened LV function (Zhang et al, 2012b;Jiang et al, 2013;Yin et al, 2015;Cong et al, 2018).…”
Section: Myocardial Pathophysiological Changes Induced By Cold Stressmentioning
confidence: 99%
“…These differences may be related to the extent and duration of cold stress in different experiments. Evaluation of cardiac function using echocardiography has indicated that cold stress decreases in ejection fraction and shortening fraction of mouse hearts, leading to dampened LV function (Zhang et al, 2012b;Jiang et al, 2013;Yin et al, 2015;Cong et al, 2018).…”
Section: Myocardial Pathophysiological Changes Induced By Cold Stressmentioning
confidence: 99%
“…However, in the present study,MDA content,which re ects the extent of cell damage [42], was decreased in the cold-exposed sheep. We speculate that the high levels of antioxidant enzymes, such as SOD [43], CAT [44], and GSH-PX [45], in plasma under cold temperature led to the degradation of the oxygen free radicals produced by sheep metabolism [46]. Studies have shown that low levels of cold stress enhance antioxidant capacity and reduce the body's exposure to the effects of oxidative stress [47].…”
Section: Discussionmentioning
confidence: 99%
“…The Least Square Adjustment (LSA) method is often used to achieve optimum solution in PAI (Tamim 1995, Wolf and Ghilani 2006, Merritt and Masters 1999, Gielsdorf et al 2004, Merritt 2005, Tong et al 2005, Casado 2006, Hope et al 2008, Tong et al 2009. LSA is used widely in the disciplines of surveying where this method is more advanced technique which adjusts observations based on the laws of probability, which models the occurrence of random errors.…”
Section: Positional Accuracy Iprovementmentioning
confidence: 99%
“…Merritt and Masters (1999) and Merritt (2005) developed the spatial adjustment engine based on the LSA to improve the accuracy of cadastral data in Australia. Tong et al (2005) presented a LSA model to resolve inconsistencies between the digitized and registered areas of cadastral parcels, and further improved the adjustment model by introducing scale parameters to reduce the influence of systematic error in the adjustment. Felus (2007) used LSA to enhance the spatial accuracy of digital cadastral maps via stochastic constraints and geometric conditions.…”
Section: Positional Accuracy Iprovementmentioning
confidence: 99%